Low-frequency noise measurements on Fe–Sn Hall sensors. (6th November 2019) - Shiogai, Junichi; Jin, Zhenhu; Satake, Yosuke; Fujiwara, Kohei; Tsukazaki, Atsushi
Abstract: Hall devices using anomalous Hall effect of ferromagnetic Fe–Sn nanocrystalline thin films exhibit high sensitivity for detection of magnetic field comparable to that of semiconductor devices. For applying this material to magnetometry, superior detectivity owing to low electrical noise is a critical requirement. We investigate the magnetic-field sensitivity and the low-frequency noise spectrum as a detectivity for Fe–Sn Hall-cross devices. We detected typical noise behavior of 1/ f and thermal noise. The noise-equivalent magnetic field reaches 0.3  μ T/Hz 1/2, which is comparable to that of semiconductor-based Hall sensors. A sufficiently low-noise spectrum evidences the potential applicability of Fe–Sn to Hall magnetometry.